THE DIFFERENCE OF ATTENTION LEVEL BEFORE AND AFTER SKIPPING EXERCISE IN MEDICAL FACULY OF DIPONEGORO UNIVERSITY STUDENTS - Azizah Indria Putri; Buwono Puruhito; Dodik Pramono; Endang Kumaidah (DIPONEGORO MEDICAL JOURNAL (JURNAL KEDOKTERAN DIPONEGORO), 2020)
Background: Skipping exercise is a kind of physical exercise which is inexpensive and easy to do. Skipping is one of many kinds of aerobic physical exercise. Aerobic physical exercise have been known from its function in improving cognitive function including attention in human brain. However there haven’t been any research which discusses about the difference of attention level before and after skipping exercise in Medical Faculty of Diponegoro University. Aim: To find out a difference of attention level before and after skipping exercise. Methods: This study conducted in quasi experimental pre-test and post-test nonequivalent group method. This study was conducted in May until July 2019. The subjects were 46 male students of Medical Faculty of Diponegoro University, divided in 2 groups. Experimental group was instructed to do 6 weeks of skipping exercise (3 times in a week) and control group was instructed to not do any exercise. Attention level was measured with software Attention Network Test a day before skipping exercise started and a day after skipping exercise ended. Significance was analyzed by Paired T Test/Wilcoxon and Independent T Test/Mann-Whitney. Results: There were no significant difference of alerting and orienting score before and after skipping exercise in both experimental and control group. Meanwhile, there was significant difference of executive control score (p=0,001) that could be seen from its first mean score 94,296 and then the score declined to be 65,130 in the second test. It indicated an increasing executive control function. Conclusion: Six weeks of skipping exercise increases executive control function of attention.Key Words: Skipping exercise, attention level, alerting, orienting, executive control